Ethno ornithology of Genus Sicalis in Mollendo, Arequipa - Pizarro Neyra, José Guillermo Celso (2021)
Some ethno-ornithological aspects of Sicalis luteola Sparrman 1789 and Sicalis raimondii Taczanowski 1874 are explained in this note. The field work take place in Mollendo, a district of Islay province, Department of Arequipa during December 2020 and January 2021. The methodology used was the interview with key informants, whose provided information about capture, breeding and competition of birds in contests at local level. Results indicate that breeders of the birds have well knowledge about the habitat of the birds. Also, information from participants about bird’s morphology and vocalization match with the literature but fail in the size of S. raimondii. Following to the participants S. raimondii is named “chollonco” while S. luteola is known as “pichí”. Another relevant information is that the capture of wild songbirds in Mollendo start from at least the first decade of the twenty century and nowadays is considered a local tradition by some dwellers.